Christian reading: language, ethics, and the order of things - Stefaniw, Blossom (University of California Press, 2019)
A narrative history of the Tura Papyri -- Reading with a grammarian -- The textual patrimony : knowledge, language and reading -- The intellectual patrimony : ethics, logic, and the order of things -- Christian reading : chronography, cartography, and genealogy